The effect of immediate "verbal" and deferred "visual verbal" feedback in improving the beating skill of volleyball - Barakat, Nouri; Salameh, Louay; Haidar, Mayada (Latakia University Journal -Medical Sciences Series, 2019)
The aim of this study was to investigate the effect of the use of verbal, verbal, and visual delayed feedback on improving the crushing beating skills of fourth year students in the field of volleyball. To achieve this, the study was conducted on a sample of 16 students who were chosen by deliberate method, They were divided into two experimental groups, the first group of (8) students, and the verbal feedback method, and the second group (8) students, who used the "visual verbal" feedback method. The results of the study showed that there were statistically significant differences between the tribal and remote measurements and the post-post benefit for both groups. This indicates that the use of the two types of feedback resulted in a positive improvement in the level of the overwhelming beating skill. The results of the study also showed no statistically significant differences The post-test between the verbal verbal feedback group and the "visual verbal" deferred feedback group at the level of overwhelming beating skill of fourth-year students specializes in volleyball. The main recommendations included the need to include the immediate and deferred feedback under consideration in the fourth year students’ Volleyball specialty" and to use it in the practical aspect when learning, improving and developing the overwhelming beating skills, as well as conducting research in the types of feedback on skills not included in the fourth year "Volleyball specialty". Other years, in order to learn their impact in learning, improving and developing volleyball skills. هدفت هذه الدراسة إلى التعرف على أثر استخدام التغذية الراجعة الفورية " اللفظية", والمؤجلة" اللفظية المرئية" على تحسين مهارة الضرب الساحق المواجه لدى طلاب السنة الرابعة تخصص كرة طائرة، ولتحقيق ذلك اجريت الدراسة على عينة قوامها (16) طالباً تم اختيارهم بالطريقة العمدية، وتم تقسيمهم إلى مجموعتين تجريبيتين المجموعة الأولى وعددهم (8) طلاب, وقد استخدم معهم أُسلوب التغذية الراجعة الفورية" اللفظية", والمجموعة الثانية وعددهم (8) طلاب, وقد استخدم معهم أُسلوب التغذية الراجعة المؤجلة" اللفظية المرئية". وقد أظهرت نتائج الدراسة في وجود فروق ذات دلالة إحصائية بين القياسين القبلي والبعدي ولصالح البعدي لكلا المجموعتين، مما يدل على أن استخدام نوعي التغذية الراجعة ادى إلى تحسن ايجابي ملحوظ في مستوى مهارة الضرب الساحق المواجه، كذلك أظهرت نتائج الدراسة عدم وجود فروق ذات دلالة احصائية على الاختبار البعدي بين أفراد مجموعة التغذية الراجعة الفورية" اللفظية" ومجموعة التغذية الراجعة المؤجلة " اللفظية المرئية" على مستوى مهارة الضرب الساحق المواجه لدى طلاب السنة الرابعة تخصص كرة طائرة. كما جاءت أبرز التوصيات, بضرورة تضمين التغذية الراجعة الفورية والمؤجلة قيد البحث في مقرر طلاب السنة الرابعة "تخصص كرة الطائرة", واستخدامها في الجانب العملي عند تعلم وتحسين وتطوير مهارة الضرب الساحق المواجه وكذلك إجراء بحوث في أنواع التغذية الراجعة على مهارات لم يشملها البحث في مقرر السنة الرابعة " تخصص كرة الطائرة" ولمقررات السنوات الأخرى, من أجل معرفة أثرها في تعلم وتحسين وتطوير مهارات الكرة الطائرة.